Setting Priorities in School Choice Enrollment Systems: Who Benefits from Placement Algorithm Preferences? - Jon Valant; Brigham Walker (Institute of Labor Economics (IZA), 2024)
Many cities with school choice programs employ algorithms to determine which applicants get seats in oversubscribed schools. This study explores whether the New Orleans placement algorithm favored students of certain races or socioeconomic classes via its use of priorities such as geographic and sibling priority. We find that when Black and White applicants submitted the same first-choice request for kindergarten, Black applicants were 9 percentage points less likely to receive it, while students in poverty were 6 percentage points less likely to receive a first-choice placement than their peers. We examine these priorities and simulate placements under alternate policies.
Keywords: I24; C78; 330; school choice; algorithm; equity; access